DAMPAK KONFLIK INTERNAL KEPEMIMPINAN PADA KINERJA DOSEN PERGURUAN TINGGI ISLAM - Adri Efferi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This paper intends to unravel the leadership internal conflict that generally happened in all State Islamic College in Indonesia, especially in the institutions named Institute (IAIN) and high school (STAIN). These issues was revealed by using case study. The selected case is STAIN Kudus in Central Java. Data were collected through interviews, observation and documentation study. The data was then analyzed using Miles and Huberman interactive model and based on the theory of transactional leadership proposed by Yulk (1998), the theory of effective leadership from Razik (1995) and models of leadership (Muhammad SAW) of Islam. The results showed that internal leadership conflicts that occurred in STAIN Kudus is the impact of 'direct election' mechanism in selecting the chairman in the late 2005. The battle between the winning and losing camps continues to become a long-drawn leadership internal conflicts. The conflicts apparently decrease the performance of the lecturers. It is characterized by shifting the focus of the lecturers‟s performances from academic to political performance.